2000
DOI: 10.1364/oe.7.000198
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of polarized light in turbid media: simulated animation sequences

Abstract: A time-resolved Monte Carlo technique was used to simulate the propagation of polarized light in turbid media. Calculated quantities include the reflection Mueller matrices, the transmission Mueller matrices, and the degree of polarization (DOP). The effects of the polarization state of the incident light and of the size of scatterers on the propagation of DOP were studied. Results are shown in animation sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…A volume concentration of 0.12% was used in the study with calculated scattering coefficient of 41cm -1 and anisotropy (the g-parameter) of 0.93. The Mueller matrix images obtained in the polystyrene solution are similar as those reported before [20][21][22][23]. The M11 component of the Mueller matrix represents the unpolarized measurements.…”
Section: Resultssupporting
confidence: 79%
“…A volume concentration of 0.12% was used in the study with calculated scattering coefficient of 41cm -1 and anisotropy (the g-parameter) of 0.93. The Mueller matrix images obtained in the polystyrene solution are similar as those reported before [20][21][22][23]. The M11 component of the Mueller matrix represents the unpolarized measurements.…”
Section: Resultssupporting
confidence: 79%
“…Through theoretical analysis, Rakovic and Kattawar 10 showed that a double-scattering model can effectively emulate the spatial patterns of backscattered light obtained from experiments. Yao and Wang 11 used a time-resolved Monte Carlo technique to present the propagation of polarized light in turbid media. All of the above studies were conducted on isotropic turbid media without considering the birefringent effect on polarizations.…”
Section: Introductionmentioning
confidence: 99%
“…The two rotating quarter wave plates technique is based upon an operational principle, which involves the modulation of a polarization state for both probing and outcoming light beams as suggested earlier by Azzam [23]. The time-resolved polarimetric imaging technique uses short pulses and time gating to distinguish between multiply scattered and weakly scattered photons where each has a different degree of polarization [24]. Several techniques have been studied to differentiate between weakly scattered and multiply scattered photons.…”
Section: Lc Devices With Applications For Polarimetric Imagingmentioning
confidence: 99%